Effectiveness of Virtual Reality-Based Balance Training Following Total Knee Replacement: A Review of Randomized Trials - S. Parekh, Saloni; Khan, Jafar; Pal, Renuka; Sharma, Deepak; Annamalai, K.M.; Lohar, Deepak; Qureshi, Abid R; Jain, Preksha; Kania, Vaishnavi; Bhatnagar, Suhani (Journal of Neonatal Surgery, 2025)
Background: According to recent Indian surveys, the prevalence of primary knee OA is high. A higher incidence of OA is consistently linked to female gender, age, and a higher BMI. Total Knee Replacement (TKR) is a common surgical option when conservative treatment options such as medication, physical therapy, and lifestyle modifications are ineffective. TKR alongwith physiotherapy is required for faster healing in such patients. Here we are comparing the effect of Virtual Reality (VR)- based rehabilitation and high-intensity exercise program for Total Knee Arthroplasty (TKA). Methods: In this randomised controlled trial, 60 participants matched the inclusion criteria who underwent Total Knee Replacement (TKR). The study was conducted for a period of 12 months from June 2024 to May 2025. The participants were randomly allotted to VR group (n=30) and a conventional group-high-intensity exercises (n=30). Outcome measures used are the Numeric Pain Rating Scale (NPRS) pain scale, knee range of motion, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Timed Up and Go (TUG) test. Result: There were significant changes in within-group differences between the experimental group and the conventional group. The range of mobility demonstrated superior results in VR-based rehabilitation compared to indifferently supporting the experimental group's pain outcome (p≥0.0001), however the numerical Pain Rating Scale substantially showed no differences between the groups. The experimental group outperformed the conventional group in terms of balance, gait, and functional activities, and the patient's functional independence was attained in nine weeks with VR-based rehabilitation as opposed to high-intensity (HI) exercises. Conclusion: The VR-based rehabilitation showed better outcomes in pain, range of motion, balance, gait and functional independence than a high-intensity exercise programme.